Valorization of by-products from commercial fish species: extraction and chemical properties of skin gelatins - Sousa, Sérgio C.; Vázquez, José A.; Pérez-Martín, Ricardo I.; Carvalho, Ana P.; Gomes, Ana M. (Molecules, 2017)
Fish skins constitute an important fraction of the enormous amount of wastes produced by the fish processing industry, part of which may be valorized through the extraction of gelatins. This research exploited the extraction and characterization of gelatins from the skin of three seawater fish species, namely yellowfin tuna (Thunnus albacares), blue shark (Prionace glauca), and greenland halibut (Reinhardtius hippoglossoides). Characterization included chemical composition, rheology, structure, texture, and molecular weight, whereas extraction studies intended to reduce costly steps during extraction process (reagents concentration, water consumption, and time of processing), while maintaining extraction efficiency. Chemical and physical characterization of the obtained gelatins revealed that the species from which the gelatin was extracted, as well as the heat treatment used, were key parameters in order to obtain a final product with specific properties. Therefore, the extraction conditions selected during gelatin production will drive its utilization into markets with well-defined specifications, where the necessity of unique products is being claimed. Such achievements are of utmost importance to the food industry, by paving the way to the introduction in the market of gelatins with distinct rheological and textural properties, which enables them to enlarge their range of applications. info:eu-repo/semantics/publishedVersion